2018
DOI: 10.1016/j.nuclphysb.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the GUP on the entropy, speed of sound, and bulk to shear viscosity ratio of an ideal QGP

Abstract: In this work we compute the entropy density, speed of sound, and the resulting impact on the bulk viscosity to shear viscosity ratio of an ideal Quark Gluon Plasma when the effects of a generalized uncertainty principle are taken into consideration. When the parameter of the generalized uncertainty principle tends to zero, i.e., α → 0, we obtain the value of the speed of sound for the ideal gas of massless particles, i.e., c 2 s → 1/3, and we recover the expected result that the bulk viscosity ζ → 0 when α → 0… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…It has been demonstrated that such a zero point length in the background geometry of spacetime can modify the low energy quantum mechanical systems, as it will modify the Heisenberg uncertainty principle to a generalized uncertainty principle [18,19,20,21]. It has also been proposed that this zero point length can be much larger than the Planck length, and this can produce effects which can be measured using present experimental data [22,23].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…It has been demonstrated that such a zero point length in the background geometry of spacetime can modify the low energy quantum mechanical systems, as it will modify the Heisenberg uncertainty principle to a generalized uncertainty principle [18,19,20,21]. It has also been proposed that this zero point length can be much larger than the Planck length, and this can produce effects which can be measured using present experimental data [22,23].…”
Section: Introductionmentioning
confidence: 79%
“…This deformation of the Heisenberg algebra would also deform the coordinate representation of the momentum operators to [18,19,20,21]. It has also been proposed that such a deformation of the Heisenberg algebra from a zero point length, much greater than the string length can be detected using optomechanical setup [24,25,26,27].…”
Section: Low Energy Quantum Systems and Zero Point Lengthmentioning
confidence: 98%
See 1 more Smart Citation
“…It is important to know that by computing the entropy density also one can find the effect of modified dispersion relation (2) on the bulk to shear viscosity ratio as an extractable quantity in relativistic heavy ion collisions [51]. Note that in a first order phase transition, some energy will be released in the medium.…”
Section: Quark-gluon Eos In Gup Model Including Minimal Length Anmentioning
confidence: 99%
“…It has been indicated that the equation of state (EoS) of an ideal Quark Gluon Plasma (QGP) is modified, when the GUP is applied, as a consequence of the modifications occurred to the corresponding thermodynamical quantities [21][22][23]. The speed of sound and the entropy density was computed after considering GUP effect on EoS of an Ideal QGP [24].…”
Section: Introductionmentioning
confidence: 99%